Wheat powdery mildew, potential damage and relations with other diseases - Linhares, Waleska I.; Ignaczak, João C.; Picinini, Edson C. (Pesquisa Agropecuaria Brasileira, 2014)
Aiming to assess the yield losses caused by powdery mildew (Erysiphe graminis DC) and its association with a complex of leaf spot diseases normally caused by Septoria nodorum, Septoria tritici and Helminthosporium sativum, trials were carried out at the National Wheat Research Center at Passo Fundo, RS, Brazil, from 1981 to 1983. The statistical design used was of completely randomised blocks with three replications. The results showed that when powdery mildew control was delayed until head stage, significant yield losses occurred; the interaction effect between powdery mildew and leaf spot complex was not significant; yield losses were observed when the leaf diseases were not controlled. Among the yield components assessed, a significant reduction in number of plants per linear meter and number of tillers per plant were observed.